1977
DOI: 10.1111/j.1471-0528.1977.tb12633.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Labour on the Lecithin/Sphingomyelin Ratio in Serial Samples of Amniotic Fluid

Abstract: Summary Serial samples of amniotic fluid were taken from 48 patients during labour. The lecithin/sphingomyelin (L/S) ratio was estimated and found to rise in 52 per cent, remain almost unchanged in 33 per cent and fall in 15 per cent. The rate of rise in the L/S ratio seemed inversely related to the length of labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The protective effect of labor is more apparent at 37-38 weeks than at 31-33 weeks (312), presumably because labor stimulates surfactant release and insufficient surfactant is stored at the earlier gestational age. Recent studies have shown that labor increases the L/S ratio and PC content of human amniotic fluid (201,(313)(314)(315). Animal studies have also shown that labor increases surfactant production (70,199).…”
Section: Other Factors Which Influence Surfactant Production In the Fmentioning
confidence: 99%
“…The protective effect of labor is more apparent at 37-38 weeks than at 31-33 weeks (312), presumably because labor stimulates surfactant release and insufficient surfactant is stored at the earlier gestational age. Recent studies have shown that labor increases the L/S ratio and PC content of human amniotic fluid (201,(313)(314)(315). Animal studies have also shown that labor increases surfactant production (70,199).…”
Section: Other Factors Which Influence Surfactant Production In the Fmentioning
confidence: 99%
“…For example, infants born by cesarean section without labor have lower concentrations of catecholamines in amniotic fluid and cord blood than do those delivered vaginally or by cesarean section after labor (I). In association with these lower catecholamine levels, infants born by cesarean section without labor have a higher incidence of breathing difficulties (2), less mature biochemical indices of lung maturity (3,4), and lower tidal volumes and lung compliance (1) than do other infants. In contrast, infants born to mothers who received P-adrenergic agonists immediately before delivery are reported to have a lower incidence of hyaline membrane disease (5).…”
mentioning
confidence: 99%